Digital Sequential Scaffolding during Experimentation in Chemistry Education—Scrutinizing Influences and Effects on Learning - Timo Fleischer; Stephanie Moser; Ines Deibl; Alexander Strahl; Simone Maier; Joerg Zumbach (Education Sciences, 2023)
Sequential scaffolding during experimentation can support students in acquiring knowledge and experimentation skills. This study aims to explore students’ understanding and perception of digital sequential scaffolds in chemistry education, investigate predictors of this understanding and perception, and examine the effects on learning outcomes and processes. A total of 183 secondary school students conducted hands-on experiments on redox reactions using digital sequential scaffolds. This study collects data through questionnaires and analyzes prior knowledge, self-perceived experimentation competence, chemistry-related self-concept, and interest as predictors. This research also examines the influence of students’ understanding and perception on cognitive and motivational learning outcomes. The findings show that learners experienced digital sequential scaffolds as helpful and were motivated by them to conduct hands-on experiments. Results also reveal that only students’ prior experience with sequential scaffolds and prior self-perceived experimentation competence significantly predict their understanding of the concept and usage of the digital sequential scaffolds. Regarding motivation, outcomes show that perceived benefit and motivation regarding experimentation predict the motivational outcomes. Overall, our findings contribute to understanding sequential scaffolding in chemistry education and inform instructional design practices.